Devolatilization non-isothermal kinetic analysis of agricultural stalks and application of TG-FT/IR analysis - Figen, Aysel Kanturk; Ismail, Osman; Piskin, Sabriye (SPRINGER, 2012)
Devolatilization behavior of several types of agricultural stalks (sunflower, rice, corn, and wheat) was studied using thermogravimetric system (TG) under nitrogen atmosphere at different heating rates (10, 15, and 20 degrees C min(-1)). Coats&Redfern, Horowitz&Metzger, and Arrhenius non-isothermal kinetic models were applied to calculate the devolatilization kinetic parameters and the devolatilization rate equations have been established. In addition, the kinetic compensation effect (KCE) has also been used to correlate pre-exponential factor (k(o)) with activation energy (E-a) and an existence of the KCE is accepted. TG-FT/IR analyses were applied of the different stalks and FT/IR stack plot used to analyze the devolatilization gas products (CO2, CH4, HCOOH, CH3OH). Infrared vibrational frequencies, micro structure and crystallinity of stalks were investigated by Fourier transform infrared spectroscopy (FT/IR), scanning electron microscope (SEM), and X-ray diffraction analysis (XRD), respectively.
Keywords: Devolatilization; Agricultural stalks; Coats & Redfern; Horowitz&Metzger; Arrhenius; TG-FT/IR; Kinetic compensation effect; PYROLYSIS; Thermodynamics; Chemistry